La législation de 1964 sur les Droits Civiques aux États-Unis : mythe d’une égalité de droit, réalité d’une égalité de fait ? - Eric Agbessi (Revue LISA)
In the USA, the congressional work on the Civil Rights Act of 1964 was part of the reassertion of the concept of citizenship, nearly one century after the amendments to the Constitution passed for this purpose in the aftermath of the Civil War. During the review of this draft law by Congressmen, conceptual opposition appeared. Indeed, and in particular among Senators, the exchange of views highlighted the fundamental differences between the Southern Democrat constitutional approach and the one bringing together Northern Democrats and Republicans for a legislative definition of citizenship. The aim was then to turn de jure into de facto equality, to put an end to the supremacy of the white community and to encourage the emergence of a form of diversity reflecting the American society of the 1960s. In this context, defining the reality of the situation means determining the content of the compromise between the two positions. As to the myth, it is the meaning in which it is understood in terms of citizenship that will be studied. The conclusion should clarify what is still myth and what has become reality to, finally, better understand what the concept of diversity is, in a democratic and multi-cultural country like the USA.